Evaluasi Penyusunan Laporan Keuangan Yayasan Menggunakan Microsoft Excel Otomatis Sesuai ISAK 335: Studi Kasus pada KJA XYZ - Tabina Aulia Catur Aryanto; Diah Hari Suryaningrum (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to evaluate the preparation of foundation financial statements by KJA XYZ using automatic Microsoft Excel and assess its compliance with ISAK 335. This research employs a qualitative descriptive approach, utilizing observation, interviews, and documentation as data collection techniques. The analysis was carried out descriptively, by presenting the results of data management in narrative form. The results of the study indicate that the preparation of foundation financial statements by KJA XYZ using Microsoft Excel is in accordance with ISAK 335, which includes financial position statements, comprehensive income statements, net asset change statements, cash flow statements, and notes to the financial statements. The use of Microsoft Excel has been proven to simplify and increase the accuracy of recording.